2023
DOI: 10.3389/fneur.2023.1074922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of whole-body vibration therapy for post-stroke spasticity: A systematic review and meta-analysis

Abstract: BackgroundOne of the main objectives of stroke rehabilitation is to alleviate post-stroke spasticity. Over the recent years, many studies have explored the potential benefits of whole-body vibration (WBV) treatment for post-stroke spasticity, but it is still controversial.ObjectiveThe current study aims to assess the efficacy and safety of WBV for post-stroke spasticity and determine the appropriate application situation.MethodsFrom their establishment until August 2022, the following databases were searched: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
1
10
1
Order By: Relevance
“…Highlighted details: The systematic review and meta-analysis by Zhang et al [ 26 ] critically assessed the impact of WBV on post-stroke spasticity. It analyzed 11 RCTs with a total of 475 patients, all of which were published in either English or Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…Highlighted details: The systematic review and meta-analysis by Zhang et al [ 26 ] critically assessed the impact of WBV on post-stroke spasticity. It analyzed 11 RCTs with a total of 475 patients, all of which were published in either English or Chinese.…”
Section: Resultsmentioning
confidence: 99%
“…The results of our analysis demonstrated the anti-spasticity effect of WBVT, which was also confirmed in previous studies ( Park et al, 2018 ; Yang et al, 2022 ). Since stroke patients may experience spasticity in various body parts ( Wissel et al, 2010 ), and a recent meta-analysis has confirmed the effectiveness of WBVT in both upper and lower extremity spasticity ( Zhang et al, 2023 ), it is essential to explore the effects of WBVT on spasticity in different body parts. However, most relevant trials did not report the specific spastic muscle groups assessed by MAS, making it difficult to determine the efficacy of WBVT for specific spastic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body vibration has been reported as effective and safe for treating spasticity in stroke patients ( Zhang et al, 2023 ). In another study, whole-body vibration rehabilitation demonstrated positive effects on the balance and gait of stroke patients ( Yin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%